Green and Efficient Processing of Wood with Supercritical CO2: A Review - Jingwen Zhang; Lin Yang; Honghai Liu (Applied Sciences, 2021)
Wood processing is a crucial step of wood utilization, but the adding of environmentally hazardous feedstocks and the use of unreasonable technology allow it to harm the environment and human health. Supercritical CO2 (scCO2) is a non-toxic, odorless, and safe solvent, which is widely used in studies and industrial production, but there is no review summarizing wood processing with scCO2. The unique structure and chemical properties of wood combined with scCO2 technology produce positive results. In this paper, wood processing with scCO2 is summarized, including wood impregnation, wood drying, wood thermochemical conversion, and wood extraction. The green and efficient characteristics of wood processing with scCO2 are explained in detail for researchers, engineers, and investors to provide a clean wood processing method. Further study is needed to reduce its energy consumption and commercialize it eventually.